DESIGN, CONSTRUCTION AND TESTING OF A PROTOTYPE HYDRO TURBINE - Janga A.A.,; Alibe M. A,; Musa A.J., (International Journal of Innovations in Engineering Research and Technology, 2023)
The world is gradually falling back to reliable, efficient and economical means of power generation that is environmentally friendly and can also be sustained on the long run. This project covers the design, construction and testing of a prototype Impulse Hydro turbine, which is a small scale machine that offers an insight to the potential and benefit of utilizing hydro energy in power generation as compared to other sources. This work covers the preliminary design considerations using established engineering calculations, the construction part which covers the manufacturing of several parts (such as the turbine buckets and wheel) by method of casting, machining and finishing, and also fabrication processes for other mechanical parts (Frame, casing, generator/alternator support etc.) like cutting, drilling, rolling, arc welding, grinding, bolting and the incorporation of the parts (both mechanical and electrical). Finally the testing of the design and its power generation are potential in relation to the intended purpose. The turbine works by receiving high pressure jet at a head of about 20m through a nozzle positioned at an angle of 1350 to the buckets arranged in an equidistant circular array, and the force of the jet propels the wheel which in turn rotates the shaft at a speed of about 210-750RPM generating an electric voltage of about 23.0V when the motion of the shaft turns the generator attached in line with it.